Factors Associated with Cataract Occurrence at the Eye Polyclinic of FMC Hospital Bogor in 2019 - Rogayah Rogayah; Deden Hermawan; Agus Isro (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
The purpose of this study was to determine the factors associated with the incidence of cataracts at the Eye Polyclinic of FMC Hospital. The method used in this research is quantitative research with analytical descriptive. This research uses a cross sectional study approach. The population of this study were all patients who visited the Eye Polyclinic of FMC Hospital Bogor. The sampling method used in this research is purposive sampling. The sample in this study was determined based on the type of cross sectional research. The incidence of cataracts is 70.6%, age 45 years is 83.8%, gender is female, which is 60.3%, work in buildings is 58.8%, history of diabetes mellitus is 66.2% , smoking habits < 20 cigarettes / day that is 40.9%. The results of statistical tests using chi-square, it can be concluded that there is a relationship between age and the incidence of cataracts (p-value 0.01; OR 5.923). There was a significant relationship between gender and the incidence of cataracts (p-value 0.002; OR 6.282). There was no significant relationship between occupation and the incidence of cataracts (p-value 0.421; OR 0.600). There was a significant relationship between a history of diabetes mellitus and the incidence of cataracts (p-value 0.005; OR 5.045). There is no significant relationship between smoking and the incidence of cataracts (p-value 0.056; OR 0.337).